2018
DOI: 10.1002/lary.27263
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after cricotracheal resection for idiopathic subglottic stenosis

Abstract: 4. Laryngoscope, 128:2268-2272, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 17 publications
3
44
0
Order By: Relevance
“…Although reports of patient complications after CTR are variable within the literature, our data appeared comparable with the reported 10% to 20% rate of anastomotic complications [26][27][28][29] and 5% to 10% rate of postoperative unilateral vocal fold paralysis. 26,27 Endoscopic Treatments A notable outcome of our study was the findings for ERMT. In this 3-year study, ERMT offered significantly improved disease control compared with ED (the most common treatment) with minimal association with voice function, particularly when compared with CTR.…”
Section: Treatment Advantages and Trade-offs Cricotracheal Resectionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although reports of patient complications after CTR are variable within the literature, our data appeared comparable with the reported 10% to 20% rate of anastomotic complications [26][27][28][29] and 5% to 10% rate of postoperative unilateral vocal fold paralysis. 26,27 Endoscopic Treatments A notable outcome of our study was the findings for ERMT. In this 3-year study, ERMT offered significantly improved disease control compared with ED (the most common treatment) with minimal association with voice function, particularly when compared with CTR.…”
Section: Treatment Advantages and Trade-offs Cricotracheal Resectionsupporting
confidence: 88%
“…Second, previous reports identified a significant rate of recurrent disease (10%-30%) among patients who underwent CTR that occurred from 5 to 10 years after the surgical procedure. [26][27][28] These outcomes were not observed in our cohort given the temporal scope of our study. Longer-term follow-up of patients who underwent CTR from our cohort will continue to address this question.…”
Section: Treatment Advantages and Trade-offs Cricotracheal Resectionmentioning
confidence: 63%
“…Treatment options for high‐grade LTS vary from endoscopic to open‐neck procedures . However, it has been reported that higher grade of stenosis purported a higher probability of its recurrence after endoscopic treatment, independently from the etiology of the stenosis itself .…”
Section: Introductionmentioning
confidence: 99%
“…This sets the background for a growing tendency in the last few decades toward open‐neck tracheal resection and anastomosis (TRA) or cricotracheal resection and anastomosis (CTRA) procedures . However, TRA and CTRA are both associated with significant postoperative morbidity, risk of failure, and functional impairments such as voice‐ and swallowing‐related problems . These potential adverse events following TRA/CTRA have motivated different authors to create new classification systems that enable precise identification of patients at risk for postoperative complications and failure of decannulation …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, cricotracheal resection places the recurrent laryngeal nerves and the cricothyroid muscles and joint at risk, which may cause permanent voice change [17]. There is also a risk of stenosis recurrence in the long term [18] which appears to be associated with the extent of the resection that needs to be performed. Conversely, implanting distant epithelial cells within the airway frequently causes chronic problems with cough and mucus, which, for some patients, effectively replaces one chronic condition (recurrent stenosis) for another (chronic cough, and mucus retention and plugging).…”
Section: Introductionmentioning
confidence: 99%